Hubungan Komunikasi Intepersonal Dengan Penyesuaian Diri - Riska Hadida; Bangun Yoga Wibowo; Arga Satrio Prabowo (Jurnal Bimbingan dan Konseling Indonesia, 2022)
The purpose of this study was to determine the relationship between interpersonal communication and self-adjustment in class X MAN 1 Kota Serang. The subjects of this study were 74 students of class X MAN 1 Kota Serang. The sampling technique used was simple random sampling. The method used in this research is quantitative method. Analysis of the data used using regression and correlation analysis. Correlation test results obtained R = 0.498, p = (p < 0.05). In this case, it can be concluded that the interpersonal communication variable has a significant positive relationship with self-adjustment. The influence of interpersonal communication on self-adjustment can be seen from the coefficient of determination (R= 0.248) indicating the effective contribution given by the interpersonal communication variable to self-adjustment is 24.8% and the remaining 75.2% is influenced by external factors in the study